Pengaruh Penguasaan Aplikasi Canva Terhadap Kinerja Guru di Sekolah Dasar Tarakanita Citra Raya [The Impact of Mastery of Canva Applications on Teacher Performance in Tarakanita Citra Raya Elementary School] - Wati, Christiana Trisna; Istighfara, Mutiara Dwima; Kumalasari, Nugraheni Sri (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2023)
Mastering information technology has become an important part of education. Teachers need to develop and master various technology applications that support learning, one of which is the Canva application. This study was conducted on 27 teachers at SD Gambar Besar Tarakanita which aimed to determine the influence of mastery of the Canva application on teacher performance. The research method used is quantitative with research instruments in the form of questionnaires. The data analysis techniques used are simple correlation test and linear regression test. The results of the correlation analysis were obtained with a ratio of 0.42 compared to the table with a significance of 0.05 obtained H0 rejected. Analysis using linear regression obtained a calculated value of 5.46979835 with N=27 at a significance degree of 5%, then H0 was rejected. The results of the study show that there is a relationship and positive influence between mastery of the Canva application and teacher performance, which means that mastery of the Canva application will improve teachers' performance in teaching. So, it can be concluded that increasing teachers' ability to use technology, especially the Canva application, can improve their performance when teaching in the classroom.